CAMPO DE CONCENTRAÇÃO: EXPERIÊNCIA LIMITE - de Magalhães, Marion Brepohl (História: Questões & Debates, 2001)
O objetivo deste artigo é o estudo de alguns aspectos da violência exercida nos campos de concentração da Alemanha nazista, considerando os elementos de cristalização que predispuseram os indivíduos a praticarem ou tolerarem o ato extremista. Analiso também, no tocante à violência contra o pensamento, as relações entre memória e História, valendo-me do testemunho de um sobrevivente que fez de toda a sua atividade intelectual um esforço para compreender o significado daquilo que tornou possível e memorável Auschwitz. Abstract The aim of this article is the study of some aspects of the violence excercised in Nazi Germanys concentration camps, taking into account the facts that led people to participate in extremely violent actions or to tolerate them. It also analyses, in terms of violence against thought, the relationship between memory and History, founded on the testimony of one of the survivors who directed all his intellectual activities to the effort of understanding the significance of all that made Auschwitz possible and unforgettable.